(untitled) (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2018)
Quite a few scientific studies carried out on the effectiveness of solvent-extracts from plant as inhibitory agents for microorganisms. A number of these studies, nevertheless, failed to report on the standard IC50 values, that would permit assessment along with other studies. Probably the most correct methods to calculate this value is via analysis of the data using nonlinear regression analysis, in which the four-parameter logistics (4PL) equation is regularly utilized by numerous scientists. In a previous study carried out from solvent extracts from Salvia officinalis, the extract was able to inhibit the bacterium Aeromonas hydrophila, a well-known fish pathogen. However, the study did not report the IC50 value for the extract. Thus, the aim of this research is to apply the four-parameter logistics equation to determine the IC50 value and its confidence interval for the plant extract. The model predicts an IC50 value of 21.92 (mg/ml) with a 95% confidence interval from 20.86 to 23.03, with a correlation coefficient value of 0.96. The result from this study allow future comparative studies to be made with other plant extracts or with other antibacterial activity using this plant extract.